The Effectiveness of the Discovery Learning Model Assisted by an Interactive Flat Panel Display on Students’ Learning Interest - Khoirul Anas; Diah Wahyuningsih (Manunggal Halim Jaya, 2026)
The background of this study lies in the importance of students’ learning interest as a primary factor in the success of the learning process in Madrasah Ibtidaiyah, as well as the need for technology-based instructional innovation to enhance student engagement and motivation. This study aims to describe the effectiveness of the discovery learning model assisted by an Interactive Flat Panel Display (IFPD) on students’ learning interest at MI Muhammadiyah Ngreco. This study employed a qualitative approach using a case study method. The research subjects consisted of one class implementing the discovery learning model supported by an Interactive Flat Panel Display. Data were collected through participatory observation, in-depth interviews with students and teachers, and documentation of learning activities. Data analysis was conducted using a descriptive-thematic approach to identify patterns and students’ perceptions related to their learning interest. The findings indicate that the implementation of the discovery learning model assisted by an Interactive Flat Panel Display positively enhances students’ learning interest. Students were observed to be more enthusiastic, active, and motivated during the learning process. The interactive media supported their engagement in exploring learning materials independently and in an enjoyable manner. In conclusion, the discovery learning model assisted by an Interactive Flat Panel Display is effective as a learning strategy to improve students’ learning interest in Madrasah Ibtidaiyah. This study recommends the broader utilization of interactive technology as an instructional innovation in educational settings.